Developing Animated Cartoons for Economic Teaching - Zhang, Yu (Journal of University Teaching and Learning Practice, 2012)
Purpose – A picture is worth a thousand words. Multimedia teaching materials have been widely adopted by teachers in Physics, Biotechnology, Psychology, Religion, Analytical Science, and Economics nowadays. To assist with engaging students in their economic study, increase learning efficiency and understanding, solve misconception problems, encourage in class discussion, and increase final performance for students (especially for international students and RA students), some animations and cartoons are developed to explain basic economic concepts for both macroeconomic and microeconomic concepts, issues and events. Methodology – Two surveys were first conducted to collect first year and international students’ requirement and suggestions. Cartoons and animations were then designed and developed to solve the major misconception and misunderstanding problems facing first year students or international students in their economic studies. Qualitative interviews were conducted to collect feedbacks for the cartoons developed for this project from economic lecturers, tutors, students and other teachers and students without economic backgrounds. Learning efficiencies from animations and text materials are also compared by the length of learning time in this paper. Findings – Surveys in this study support the view that different students have different preferred learning methods. However, practice case studies are the preferred learning method for both first year university students and international students. The animated cartoons developed in this research received strong positive feedbacks from peer colleagues in Economics, teachers from other faculties, tutors in Economics, first year students, international students and RA students with dyslexic problems. Utilisation of these resources can improve learning efficiency, help students in their understanding and long-term memory of the subject, engage students in their studies, and increase interest in undertaking economic studies amongst all other students. Value – The results of this study could be used in any Economics subject, as well as for self-study by Economics students and others. As part of the Teaching and Learning Project, these materials are capable of being further used in mobile applications to assist in engaging students in their learning.